From the Editor: The New Normal?. (June 2021) - Kelly, Rob
Abstract : Hopefully, by the time you read this, the world will have turned the corner on the COVID-19 pandemic in reality instead of in press conferences, with the vaccines becoming more and more available, and vaccine hesitancy becoming less and less common. Looking back, I can see how much has changed. Some things will come back, and they will be great, with hugs and handshakes between friends and loved ones being one of my favorites. Masks are a pain in the rear, particularly for those who wear glasses, but having to greet from a distance is something that I will miss even less. Social gatherings will be back, including at in-person conferences (a word from our sponsor: maybe the 240th ECS Meeting in Orlando, October 10-14). I realize more than ever that these meetings are the only time that I see some people, especially those outside my specialty. Catching up over a meal and an adult beverage or two is the best way to spend evenings at the meetings.